The Implementation Of Government Regulation No. 86 Of 2018 On Agrarian Reform In Connection With Law No. 5 Of 1960 On The Basic Agrarian Law - Utami, Annisa Nur; Rahayu, Mella Ismelina Farma (UNIVERSITAS PAKUAN, 2020)
This research discusses the implementation of agrarian reform and land registration in Indonesia, with a focus on the correlation between the Land Registration Information System (PTSL) and the Basic Agrarian Law (UUPA). The study examines the process of implementing agrarian reform in the village of Lontar, Tirtayasa Subdistrict, Serang Regency, and analyzes changes in land ownership structure to determine the effectiveness of agrarian reform in promoting equitable land ownership. The correlation between PTSL and UUPA, when viewed from the implementation of government programs, PTSL is a program implemented by the government as part of efforts to enhance legal certainty and systematic land management. UUPA provides a legal foundation for the government to implement the PTSL program, including aspects such as land acquisition, compensation, and spatial planning Agrarian reform remains an important thing to do in Indonesia given the high cases of land or land conflicts that occur. One of the contributing factors is the lack of clarity of the map that is a reference for all parties concerned. To follow the national land policy, the implementation of agrarian resource management needs to be carried out through six activities, namely: land use arrangement, land tenure regulation, land parcel data collection, granting land rights, registering land rights and their transition (certification), and resolving land disputes. To carry out the management of agrarian resources, proper, accurate, and strong database administration is needed.